Effectiveness of PainAway® on hepatitis B intramuscular injection in term neonates: a randomized controlled trial - Susilawati Susilawati; Soetjiningsih Soetjiningsih; Bagus Ngurah Putu Arhana; Ida Bagus Subanada (Paediatrica Indonesiana, 2010)
Background Routine immunization injections are the mostcommon painful procedure in childhood and most of theseinjections are administered in early life. Immunizations can causenegative short- and long-term consequences for children. Childrenwho experience high levels of pain during an immunizationare more likely to have elevated distress level of subsequentinjections.Objective To evaluate the effectiveness of pain away in reducingpain associated with hepatitis B intramuscular injection in termneonates.Methods An open randomized controlled trial on healthy termneonates was conducted between November 2009 and December2009 at Sanglah Hospital in Denpasar, Bali. Subject were selectedrandomized using six-blocked randomization. The sampleswere divided into two groupsto either recieve intramuscularhepatitis B injection using PainAway® and or standard hepatitisB intramuscular injection. The pain response was assessed usingDouleur Aiquedu Noureanu-né(DAN) scale. Mann-Whitney testwas used to analyze the data. The confounding factor that mayhave influenced the pain response was analyzed using multivariateanalysis (ANCOVA).Results Out of 66 subject, DAN scale was significantly lower inintervention group (median 5.0) compared to control (median 7.0)with P < 0.0001. Multivariate analysis showed that the differencein the intervention given was the only variable that influencedthe pain response (P < 0.0001).Conclusion PainAway® can reduce the pain secondary tohepatitis B intramuscular injection on term neonates.